Le vie chirurgiche conservative: anca - Brioschi, M.; Favilla, S.; Pace, F.; Giai Via, A.; Randelli, F. (Lo Scalpello - Journal, 2018)
CONSERVATIVE SURGICAL APPROACHES: THE HIP The most common conservative approaches to the hip joint are the anterior, the Ganz safe surgical dislocation and the medial approach. The anatomy of these approaches is described in detail in this review. Each approach is also evaluated considering the surgical conservative indications, technique, and complications.